Peningkatan Tekstur Permen Jeli dengan Porang (Amorphophallus oncophyllus) dan Gelatin: Peningkatan Tekstur Permen Jeli dengan Porang (Amorphophallus oncophyllus) dan Gelatin - Imroatul Anifa; Veriani Aprilia; Arif Sabta Aji; Nurul Kusumawardani; Rizal Fauzi; Daru Estiningsih; Effatul Afifah (Amerta Nutrition, 2026)
Background: Porang (Amorphophallus oncophyllus), a native Indonesian tuber, is rich in glucomannan and proved to have antihyperglycemic properties. Its effect is further amplified when porang was macerated with keji beling (Strobilanthes crispus). In the food industry, porang is commonly utilized as a gelling agent in jelly candies, although it tends to produce a soft gel texture. To improve the gel texture, glucomannan can be combined with gelatin. Objectives: This study aimed to investigate the impact of gelatin on the texture profile, moisture content, ash content, and protein content of jelly candies made from porang. Methods: The study employed an experimental approach with a completely randomized design. The jelly candy samples were prepared using porang macerated with keji beling, with gelatin concentrations varying at 0%, 7.5%, 10%, and 12.5%. The texture profile of the candies was assessed using a texture analyzer. Results: The incorporation of gelatin significantly enhanced the texture profile of the jelly candies, including improvements in hardness (40.38–64.54 N), cohesiveness (0.41–0.65), gumminess (17.25–42.59 N), springiness index (0.74–0.93), and chewiness (12.99–39.66 Nmm). Additionally, the protein content of the jelly candies increased from 1.30% to 12.10%, while the ash content decreased from 1.54% to 1.41%, and the moisture content decreased from 67.99% to 61.52%. Conclusions: The addition of gelatin positively influenced the texture profile of the jelly candies. This product holds potential for development as a functional local food.